Impact of COVID-19 related delays on outcome of intertrochanteric neck femur fractures - Yeotiwad, Ganesh R.; Argekar, Harshad G.; Upadhyaya, Mohit R.; Bhardwaj, Lakshya L.; Yadav, Amit S. (International Journal of Research in Orthopaedics, 2023)
Background: We are aware of no other study that has examined how the epidemic has affected an emergency service. Hence, the present study aims to determine the functional outcomes of delayed fixation to understand the impact of COVID-19 related hindrance to emergency service. Methods: During the 1st wave of COVID-19, prevailing staff shortages and need for COVID tests resulted in minimum delay of 10 days between admission and surgeries as compared to the recommended urgent fixation standard. Harris Hip Score was calculated at 1 year follow up for these patients. Results: The results showed that the mean age of the patients was 68.65±8.03 years. Out of all the patients, 50.9% were males and 49.1% were females. The mean Harris Hip score at 1 year follow-up was 78.76±11.65. Out of all, 3.63% were lost to follow up, and 20% were expired. Conclusions: Early surgery seems to improve survival and decline in pressure sores. Conservative management should be well planned and used on patients who actually have a good risk to benefit ratio to it as the patients can develop increased risk of pulmonary, skin, and urinary infections. Efforts should be made to operate patients on within one to two days. Despite the fact that the overall number of trauma cases declined in this unprecedented COVID-19 scenario.